ANALISIS PENGARUH PARTISIPASI ANGGARAN DAN GAYA KEPEMIMPINAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Syahdinar Govinda Hutama; Endah Susilowati (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2021)
The Covid-19 pandemic is a momentum for the industry to grow in response to several rules imposed during the pandemic. This development is often referred to as the digitalization of technology in various fields of life, including large and small companies. Digitization will affect managerial performance directly, in this study the factors that influence it include budgetary participation and leadership style and organizational commitment as an intervening variable with the Office of the Class 1 Surabaya Monitoring Center which is under the auspices of the Minister of Communication and Information as the object of research. This study aims to determine how organizational commitment affects the relationship between budget participation and leadership style on managerial performance. The sample in this study were 35 employees at the Balai Monitor Office Class 1 Surabaya using the purpose sampling method. The analysis of the results was carried out through the stages of convergent validity, discriminant validity, reliability testing, R-Square, and hypothesis testing. The research was processed using SmartPLS 3.0 software. Based on the results of the study, it shows that budgetary participation and leadership style have a positive and significant effect on managerial performance, while organizational commitment has no positive and significant effect on managerial performance. Budget participation has a positive and significant effect on organizational commitment, while leadership styles have no positive and significant effect on organizational commitment. Organizational commitment cannot be an intervening variable that affects the relationship between budget participation and leadership style on managerial performance. Keywords: participation, leadership, commitment, managerial performance